Effectiveness of a Selective Integrative Counseling Program to Enhance Self-Compassion and Improve Mental Health in an Intersex Case Following Sex Reassignment Surgery: A Case Study - Dr. Asma Mohammed Mustafa Dafaalla* (الآداب للدراسات النفسية والتربوية, 2025)
This study aimed to examine the effectiveness of an integrative eclectic counseling program that combines Cognitive Behavioral Therapy (CBT), Acceptance and Commitment Therapy (ACT), and Dialectical Behavior Therapy (DBT) in enhancing self-compassion and improving mental health in an intersex individual who underwent sex reassignment. Pre-assessment results indicated a significant deficiency in self-compassion, characterized by high self-criticism, emotional dysregulation, and disconnection from common humanity, in addition to elevated levels of psychological distress—particularly anxiety, depression, and social dysfunction. A single-case pre-post design was used, and the program was tailored to the individual's cognitive, emotional, and social needs. It consisted of 20 individual sessions over a period of three months. Post-intervention results showed a marked improvement in self-compassion and a significant reduction in symptoms of anxiety, depression, and social dysfunction. These findings highlight the effectiveness of the integrative counseling approach in alleviating psychological suffering and promoting adaptation to gender identity-related stressors and medical experiences. The study underscores the importance of designing interventions that consider identity and emotional dimensions for intersex individuals' post-reassignment.